Treatment of gynecological cancers diagnosed during pregnancy. (October 2016) - Halaska, Michael J; Rob, Lukas; Robova, Helena; Cerny, Milos
Because of a notable increase in age at delivery, the incidence of malignancy diagnosed during pregnancy has substantially increased. This review aims to summarize the literature and expert knowledge on gynecologic cancers diagnosed in pregnancy regarding epidemiology, examination and staging procedures, description of treatment modalities and management of gynecological malignancies with special interest in cervical and ovarian cancer. Thorough attention is paid to the surgery and chemotherapy administration for early-stage cervical cancer diagnosed during pregnancy.